Proposal for Barquisimeto´s historical center´s connectivity with other sectors of the city (Gaceta Técnica, 2020)
A series of urban proposals is presented below, designed to connect the historic center of the city of Barquisimeto in Venezuela, with other sectors of the city. Large buildings where different legislative, administrative and judicial bodies of the Lara State operate in an area surround Works of great architectural and historical value dating from the 19th century stand out, with touches of modernity since it. The proposals involved correspond to the design of super blocks, a network of bicycle lanes, a university transportation system called UCLA University Route, and a large historical library. All this in order to achieve connectivity not only from a spatial point of view through mobility systems, but also through the emotional connection of the citizen to that sector, achieving that attachment or sense of belonging
Keywords: Barquisimeto old town; super blocks; bike paths; mansion Mayda